Primary Atypical Carcinoid Tumour of the Sphenoid Sinus Rostrum - Kate A. Stephenson; Darlene E. Lubbe (Case Reports in Otolaryngology)
Primary carcinoid tumors of the nasal cavity and sinuses are exceedingly rare. An accurate histopathological diagnosis is crucial to optimal investigation and management. We present a case of a primary atypical carcinoid tumor arising from the sphenoid rostrum without evidence of associated carcinoid syndrome. This rare but important differential diagnosis of a nasal tumor is discussed and important unique management issues are highlighted.